Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Socio-economic impacts of private land use investment on rural communities: Industrial forest plantations in Niassa, Mozambique - Bleyer, Maja; Kniivilä, Matleena; Horne, Paula; Sitoe, Almeida; Falcão, Mário Paulo (Land Use Policy, 2016)
East Africa has experienced an increase of private land use investments in the past years. Rural households have consequently faced crucial changes in their livelihoods. This paper explores the socio-economic impacts of industrial forest plantations on rural communities in Niassa, Mozambique. According to our results private forest plantations have the potential to positively impact local people’s wealth and well-being, if enough emphasis is given to minimizing the negative impacts. The household survey data of 218 observations from five villages were analyzed using binary and multinomial logistic regression analyses. The study shows that forest plantations have threatened the basis of traditional rural livelihoods by reducing the availability of natural resources and through the relocation of agricultural plots. However, investments have also supported the diversification of livelihood strategies in the communities by providing formal employment and by increasing business and trading activities. As growing population and traditional agricultural practices have led to the overexploitation of natural resources, non-natural resource-based livelihood strategies increase the resilience of a household. The majority of respondents reported plantations to have either no overall impact or a positive impact on the well-being of their household. According to our results, socio-economic household characteristics only marginally explain respondents’ perceptions of the impacts of forest plantations but perceptions differ significantly between individual villages.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - english / inglês; agriculture / agricultura; governance / governação; land governance / gestão de terra; private sector / setor privado

Corporate Social Responsibility in Mozambique - Kaufmann, Friedrich; Simons-Kaufmann, Claudia (Corporate Social Responsibility in Sub-Saharan Africa: Sustainable Development in its Embryonic Form, 2016)
Mozambique is a young African country with a strong growing economy and increasing foreign direct investment. We can observe a rising number of Corporate Social Responsibility (CSR) projects and activities in the country. Nevertheless there is still no systematic approach or coordination through public authorities or the business sector itself. CSR is mainly motivated by immediate own company needs like training or health of workers. We also find philanthropy projects as well as projects supporting local communities on development priorities, mainly health, education and community development. CSR, as part of a business concept, is mainly limited to large companies and foreign investors with international experience and less to small and medium-sized enterprises (SMEs). Many national companies, especially SMEs still do not have the CSR capacity or the respective mind set. First of all it is the mega projects that have their professional CSR departments and budgets. In the mining sector a CSR component is now compulsory by law since 2014.As public institutions are weak, CSR in Mozambique is more about “CSR towards compliance” and sometimes less about “CSR beyond compliance”. Strong views are expressed by civil society that for example the enforcement of labour legislation within companies is weak and hardly controllable by the government. This fact combined with corruption issues makes CSR towards compliance of existing labour, environmental, fiscal laws and other regulation an important topic. Nevertheless it is questionable if this should be considered as CSR. CSR in general is sometimes seen as “green washing” by big investors, benefitting on the other hand from generous tax exemptions and special deals with the government. Nevertheless, CSR is of growing importance in Mozambique and as the new mining CSR law shows, government is slowly entering the CSR landscape. A better coordination and public-private dialogue about CSR is necessary in order to make it a more useful and an efficient instrument for development. Nevertheless it should be clear that CSR is voluntary and in a globalized economy with international value chains becomes more and more an international issue.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; private sector - CSR (corporate social responsibility) / setor privado - RSC (responsabilidade social corporativa); private sector / setor privado